Fire preventing and extinguishing adhesive gel for top of coal mine goaf, preparation method and application

Through the combination of nanoclay-polydopamine composite material and sodium alginate, a fire-fighting adhesive gel with an interpenetrating grid structure is formed, which solves the problem of poor gel adhesion in the existing technology and realizes the top of the coal mine goaf efficient fire prevention and extinguishing effect.

CN119258476APending Publication Date: 2025-01-07SHANGHAI DATUN ENERGY +2

Patent Information

Application Number
CN202411395952.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing mine fire-fighting gel has problems of weak adhesion and easy to fall off when applied to the top of the coal mine goaf, making it difficult to effectively prevent coal spontaneous combustion.

Method used

The nanoclay-polydopamine composite material is combined with sodium alginate solution to form an interpenetrating grid structure through hydrogen bonding and covalent interaction to prepare a fire-fighting adhesive gel with excellent adhesion properties.

Benefits of technology

It significantly improves the adhesion and fire-fighting properties of the gel, reduces material consumption, extends usage time, enhances the isolation effect of coal, and effectively prevents coal spontaneous combustion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses fire preventing and extinguishing adhesive gel for the top of a coal mine goaf, a preparation method and application, and relates to the technical field of mine fire preventing and extinguishing. The method comprises the following steps: firstly, preparing a sodium alginate solution, then preparing a nano-clay-polydopamine composite material, and mixing and stirring the nano-clay-polydopamine composite material and the sodium alginate solution to obtain a mixed solution I; adding a sodium hydroxide aqueous solution into acrylic acid for partial neutralization, and adding the mixed solution I into the neutralized solution to obtain a mixed solution II; adding an initiator and a cross-linking agent into the mixed solution II, and uniformly stirring to obtain a mixed solution III; and finally, stirring the mixed solution III at a certain temperature to form gel, thereby obtaining the product. The prepared fire preventing and extinguishing gel is especially suitable for the top of a coal mine goaf, and shows excellent leakage stoppage performance, inhibition performance, adhesion and water-retaining performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fire prevention and extinguishing for mines, and in particular to a fire prevention and extinguishing adhesive gel used for the top of a coal mine goaf, a preparation method and an application thereof. Background Art

[0002] Coal is an important energy source in the world. The steel, power industry and other industries have a great demand for coal. With the increase in the intensity of coal mining, disasters and accidents occur from time to time. Among them, fires caused by spontaneous combustion of coal are one of the major fires, which not only cause the loss of coal resources, but also produce a large amount of toxic and harmful gases, posing a serious threat to the environment and personnel health. Therefore, the prevention and control of mine fires is the key to ensuring the safe mining of coal mines. In coal mining, gel-based fire-fighting materials have excellent cooling and air leakage plugging properties, strong water retention and controllable gelation time. They have broad application prospects in controlling spontaneous combustion of coal in goafs and plugging air leakage channels in goafs. At present, researchers have proposed mining gels such as water glass gel, composite gel, and polymer gel.

[0003] The research reports on the existing technology of fire extinguishing gel for mines are as follows:

[0004] Application No. 202011059830.3 discloses a fire-proof gel material for mining and a preparation method thereof. The material is formed by mixing a solid mixture with water at a water-to-solid ratio of 6-16:1. The solid mixture includes the following components by weight: 11-14 parts of solid water glass, 6-8 parts of accelerator, 12-16 parts of fly ash, 10-14 parts of activator, 4-8 parts of magnesium aluminum silicate and 40-60 parts of sodium bentonite; the modulus of solid water glass is 2.0-2.5. By adjusting the water-to-solid ratio and adding water to the solid mixture, a fire-proof gel with strong water retention, high mechanical strength and adjustable gelation time is provided. Application No. 202311202427.5 discloses a hydrogel fire extinguishing material for mining and a preparation method thereof, the method comprising: step 1, mixing solid water glass, sodium bicarbonate, polyvinyl alcohol and silicon carbide and stirring evenly to obtain a solid mixture; step 2, adding water to the solid mixture and stirring evenly to obtain a hydrogel fire extinguishing material. Application No. 202410518409.6 discloses a method for preparing a steel slag-based fire extinguishing gel material for mining, comprising the following steps: (1) mixing steel slag, silica ash and Al2O3 to obtain a solid mixture; (2) mixing the solid mixture obtained in step (1), an alkali activator and water to obtain a slurry; (3) adding a coagulant to the slurry obtained in step (2), pouring it into a mold after the reaction, and letting it stand to form a gel to obtain a steel slag-based fire extinguishing gel material for mining.

[0005] Although the fire-proofing gel material in the prior art has played a certain role in preventing and controlling coal spontaneous combustion, it has the disadvantages of weak adhesion and easy falling off when applied on the top of the goaf.

[0006] This shows that the prior art needs to be further improved. Summary of the invention

[0007] One of the purposes of the present invention is to provide a method for preparing a fire-proof adhesive gel for the top of a coal mine goaf. The prepared gel is particularly suitable for the top of a coal mine goaf and exhibits excellent leak-proofing, chemical resistance, adhesion and water retention.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] A method for preparing a fire-proof adhesive gel for use on the top of a coal mine goaf comprises the following steps:

[0010] (1) Preparing a sodium alginate solution: dissolving a certain amount of sodium alginate powder in distilled water, stirring and heating at a certain temperature to form a uniform solution;

[0011] (2) preparing a nanoclay-polydopamine composite material: mixing a nanoclay suspension with dopamine, and then adding a buffer solution, so that under alkaline conditions, dopamine enters the interlayers of the nanoclay with a layered structure and polymerizes in situ to form a nanoclay-polydopamine composite material;

[0012] (3) mixing the nanoclay-polydopamine composite material with the sodium alginate solution and stirring to obtain a mixed solution 1;

[0013] (4) adding sodium hydroxide aqueous solution to acrylic acid for partial neutralization, and adding the mixed solution 1 to the neutralized solution to obtain a mixed solution 2; adding an initiator and a cross-linking agent to the mixed solution 2, and stirring to obtain a mixed solution 3;

[0014] (5) The mixed solution is stirred at a certain temperature to form a gel. During the gelation process, acrylic acid is free radical polymerized under the action of an initiator and a cross-linking agent to form polyacrylic acid. The molecular chains of polyacrylic acid and sodium alginate form an interpenetrating grid structure through hydrogen bond interaction. The catechol groups contained in the nanoclay-polydopamine composite material form hydrogen bond interactions with the hydroxyl groups of polyacrylic acid and sodium alginate to obtain a fire-proof adhesive gel.

[0015] In the above-mentioned method for preparing the fire-proof adhesive gel for the top of the coal mine goaf, in step (1), the mass fraction of sodium alginate in the sodium alginate solution is 1-3%, and the temperature is 40-50°C.

[0016] In the above-mentioned method for preparing a fire-proof adhesive gel for the top of a coal mine goaf, in step (2), the preparation steps of the nanoclay suspension are: mechanically crushing bentonite and removing impurities; then wet grinding to peel off the layered structure of the bentonite into a nano-scale multi-layer structure; dispersing the bentonite obtained by mechanical crushing in water to form a uniform suspension.

[0017] In the above-mentioned method for preparing a fire-proof adhesive gel for the top of a coal mine goaf, in step (2), the buffer solution is a methylaminomethane-Tris buffer solution, the pH value under alkaline conditions is 8-9, and the mass ratio of the nanosuspension to dopamine is 1:2.

[0018] In the above-mentioned method for preparing the fire-proof adhesive gel for the top of the coal mine goaf, in step (3), the volume ratio of the nanoclay-polydopamine composite material to the sodium alginate solution is 1:1.

[0019] In the above-mentioned method for preparing the fire-proof adhesive gel for the top of the coal mine goaf, in step (4), sodium hydroxide aqueous solution is added to acrylic acid for neutralization, and after 70% neutralization, it is mixed with the mixed solution.

[0020] The above-mentioned method for preparing a fire-proof adhesive gel for the top of a coal mine goaf, in step (4), the initiator is a potassium persulfate solution, and the cross-linking agent is an aqueous solution of N,N-methylenebisacrylamide; the mass fraction of potassium sulfate in the potassium sulfate solution is 3-6%, and the mass fraction of N,N-methylenebisacrylamide is 2-3%; the volume ratio of the mixed solution II, the initiator, and the cross-linking agent is 12:1:1.

[0021] Another object of the present invention is to provide a fire-proof and extinguishing adhesive gel prepared by the above-mentioned preparation method.

[0022] Another object of the present invention is to provide an application of the above-mentioned fire-proof and extinguishing adhesive gel, characterized in that the application is to spray the adhesive gel on the surface of coal to prevent spontaneous combustion of coal by reducing the oxygen-containing functional groups of the coal and isolating the coal from oxygen.

[0023] The preparation mechanism of the fire-proof and extinguishing adhesive gel of the present invention is:

[0024] First, acrylic acid polymerizes with free radicals under the action of initiators and crosslinkers to form polyacrylic acid, and then the polyacrylic acid molecular chain and sodium alginate interact through hydrogen bonds to form an interpenetrating network structure. Finally, the added nanoclay-polydopamine composite material forms hydrogen bonds with the hydroxyl (-OH) of polyacrylic acid and sodium alginate through the catechol groups it contains. Under the action of crosslinkers and initiators, the three form a fire-proof adhesive gel.

[0025] Compared with the prior art, the present invention brings the following beneficial technical effects:

[0026] (1) The present invention utilizes the catechol groups contained in the nanoclay-polydopamine composite material to form hydrogen bond interactions with the hydroxyl groups of polyacrylic acid and sodium alginate to obtain an anti-fire extinguishing adhesive gel; the nanoclay is prepared using bentonite, which has a layered structure, and when the nanoclay suspension is mixed with dopamine, dopamine intercalation can be achieved. The nanoclay-polydopamine composite material contains a large number of catechol groups, which can produce a lasting adhesion effect with the matrix through covalent interactions and non-covalent interactions such as π-π interactions, cation-π interactions, metal coordination, and hydrogen bonds. The nanoclay-polydopamine composite material is particularly suitable for solving the problem of poor adhesion of existing mine-use anti-fire extinguishing gels, so that the mine-use anti-fire extinguishing gel has excellent fire extinguishing performance and adhesion performance, and can more effectively prevent coal spontaneous combustion.

[0027] (2) The fire-proof adhesive gel prepared by the present invention has strong adhesive properties, which can effectively solve the problem that traditional gel is easy to fall off at the top of the goaf, increase the use time of the gel, reduce the consumption of gel materials, and thus reduce the material loss cost.

[0028] (3) The fire-proof adhesive gel prepared by the present invention has good water retention. On the one hand, the gap between the coal and the gel is tighter, reducing the inflow of air. On the other hand, the fire-proof adhesive gel better isolates the coal from oxygen, significantly improving the fire-proof performance, thereby preventing the spontaneous combustion of coal. DETAILED DESCRIPTION

[0029] The present invention proposes a fire-proof adhesive gel for the top of a coal mine goaf, a preparation method and an application thereof. In order to make the advantages and technical solutions of the present invention clearer and more specific, the present invention is further described below in conjunction with specific embodiments.

[0030] In the description of the present application, the words "mixed solution one", "mixed solution two" and the like are only used to distinguish different objects, and do not limit the quantity and execution order, and the words "mixed solution one", "mixed solution two" and the like do not necessarily limit the difference. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.

[0031] The technical solution of the present application is described in further detail below.

[0032] A method for preparing a fire-proof adhesive gel for use on the top of a coal mine goaf comprises the following steps:

[0033] (1) Preparation of sodium alginate solution: dissolving a certain amount of sodium alginate powder in distilled water, wherein the mass fraction of sodium alginate in the sodium alginate solution is 1-3%, and stirring and heating at a temperature of 40-50° C. to form a uniform solution.

[0034] (2) Preparation of nanoclay-polydopamine composite materials:

[0035] Preparation of nanoclay suspension: Mechanically crush bentonite to reduce particle size, remove impurities and improve the purity of bentonite; then wet grind to peel off the layered structure of bentonite into a nano-scale multi-layer structure; disperse the peeled bentonite in water to form a uniform suspension.

[0036] The suspension of nanoclay is mixed with dopamine, and then a buffer solution is added. Under alkaline conditions, dopamine enters the interlayers of the nanoclay with a layered structure and polymerizes in situ to form a nanoclay-polydopamine composite material.

[0037] The above-mentioned buffer solution is preferably a methylaminomethane-Tris buffer solution, the pH value of which is 8-9 under alkaline conditions, and the mass ratio of the nanosuspension to dopamine is 1:2.

[0038] The nanoclay-polydopamine composite material is obtained by in-situ polymerization using nanoclay as a carrier, wherein the catechol groups of polydopamine can form hydrogen bonds or covalent bonds with the hydroxyl groups on the surface of the nanoclay, thereby enhancing the stability of the composite material.

[0039] (3) Mixing the nanoclay-polydopamine composite material with the sodium alginate solution and stirring to obtain a mixed solution 1. More preferably, the volume ratio of the nanoclay-polydopamine composite material to the sodium alginate solution is 1:1.

[0040] (4) adding an aqueous sodium hydroxide solution to acrylic acid for partial neutralization, so that an esterification reaction occurs between acrylic acid molecules to form a cross-linked structure; after 70% neutralization, the solution is mixed with mixed solution 1 to obtain mixed solution 2; adding an initiator potassium persulfate solution and an aqueous solution of a cross-linking agent N,N-methylenebisacrylamide to mixed solution 2, and stirring the mixture to obtain mixed solution 3.

[0041] Preferably, the mass fraction of potassium sulfate in the potassium sulfate solution is 3-6%, and the mass fraction of N,N-methylenebisacrylamide is 2-3%; the volume ratio of the mixed solution II, the initiator, and the cross-linking agent is 12:1:1.

[0042] (5) The mixed solution is stirred at a certain temperature to form a gel. During the gelation process, acrylic acid is free radical polymerized under the action of an initiator and a cross-linking agent to form polyacrylic acid. The molecular chains of polyacrylic acid and sodium alginate form an interpenetrating grid structure through hydrogen bond interaction. The catechol groups contained in the nanoclay-polydopamine composite material form hydrogen bond interactions with the hydroxyl groups of polyacrylic acid and sodium alginate to obtain a fire-proof adhesive gel.

[0043] The present invention will be further described below in conjunction with specific embodiments.

[0044] Embodiment 1:

[0045] A method for preparing a fire-proof adhesive gel for use on the top of a coal mine goaf, the specific steps are as follows:

[0046] (1) Weigh sodium alginate powder and dissolve it in distilled water. Stir and heat in a 45°C water bath to form a uniform solution. The mass fraction of sodium alginate is 2%.

[0047] (2) mixing the nanoclay suspension with dopamine to achieve dopamine intercalation, adding methylaminomethane-Tris buffer solution, and under alkaline conditions (usually pH value of about 8.5), dopamine undergoes in-situ polymerization between nanoclay layers to form a nanoclay-polydopamine composite material;

[0048] (3) mixing the nanoclay-polydopamine composite material obtained in step (2) and the sodium alginate solution obtained in step (1) in a volume ratio of 1:1 and stirring to form a uniform solution, thereby obtaining a mixed solution 1.

[0049] (4) adding sodium hydroxide aqueous solution to acrylic acid for partial neutralization, and mixing it with mixed solution 1 after 70% neutralization to obtain mixed solution 2; adding initiator potassium persulfate solution and crosslinking agent N,N-methylenebisacrylamide aqueous solution to mixed solution 2, and stirring uniformly to obtain mixed solution 3.

[0050] (5) The mixed solution 3 was slowly stirred in a 45° C. water bath to obtain a fire-resistant adhesive gel after 20 minutes.

[0051] Embodiment 2:

[0052] A method for preparing a fire-proof adhesive gel for use on the top of a coal mine goaf, the specific steps are as follows:

[0053] (1) Weigh sodium alginate powder and dissolve it in distilled water. Stir and heat in a 40° C. water bath to form a uniform solution. The mass fraction of sodium alginate is 1%.

[0054] (2) mixing the nanoclay suspension with dopamine to achieve dopamine intercalation, adding methylaminomethane-Tris buffer solution, and under alkaline conditions (usually pH value of about 8.5), dopamine undergoes in-situ polymerization between nanoclay layers to form a nanoclay-polydopamine composite material;

[0055] (3) mixing the nanoclay-polydopamine composite material obtained in step (2) and the sodium alginate solution obtained in step (1) in a volume ratio of 1:1 and stirring to form a uniform solution, thereby obtaining a mixed solution 1.

[0056] (4) adding an aqueous sodium hydroxide solution to acrylic acid for partial neutralization, and mixing it with mixed solution one after 100% neutralization to obtain mixed solution two; adding an initiator potassium persulfate solution and an aqueous solution of a cross-linking agent N,N-methylenebisacrylamide to mixed solution two, and stirring them uniformly to obtain mixed solution three.

[0057] (5) The mixed solution 3 was slowly stirred in a 45° C. water bath to obtain a fire-resistant adhesive gel after 20 minutes.

[0058] Embodiment 3:

[0059] A method for preparing a fire-proof adhesive gel for use on the top of a coal mine goaf, the specific steps are as follows:

[0060] (1) Weigh sodium alginate powder and dissolve it in distilled water. Stir and heat in a 50° C. water bath to form a uniform solution. The mass fraction of sodium alginate is 3%.

[0061] (2) mixing the nanoclay suspension with dopamine to achieve dopamine intercalation, adding methylaminomethane-Tris buffer solution, and under alkaline conditions (usually pH value of about 8.5), dopamine undergoes in-situ polymerization between nanoclay layers to form a nanoclay-polydopamine composite material;

[0062] (3) mixing the nanoclay-polydopamine composite material obtained in step (2) and the sodium alginate solution obtained in step (1) in a volume ratio of 1:1 and stirring to form a uniform solution, thereby obtaining a mixed solution 1.

[0063] (4) adding sodium hydroxide aqueous solution to acrylic acid for partial neutralization, and mixing it with mixed solution 1 after 60% neutralization to obtain mixed solution 2; adding initiator potassium persulfate solution and crosslinking agent N,N-methylenebisacrylamide aqueous solution to mixed solution 2, and stirring uniformly to obtain mixed solution 3.

[0064] (5) The mixed solution 3 was slowly stirred in a 45° C. water bath to obtain a fire-resistant adhesive gel after 20 minutes.

[0065] Comparative Example 1:

[0066] A method for preparing a fire-proof adhesive gel comprises the following steps:

[0067] (1) Weighing acrylic acid powder (2 wt%) and dissolving it in distilled water, heating it in a 45° C. water bath with stirring for 20 min to form a uniform solution;

[0068] (2) adding sodium hydroxide aqueous solution (pH 10) to acrylic acid and stirring evenly to make the neutralization degree of acrylic acid reach 70%;

[0069] (3) An initiator potassium persulfate (APS) aqueous solution and a cross-linking agent N,N-methylenebisacrylamide (MBA) aqueous solution are sequentially added to the solution obtained in step (2), wherein the mass fraction of APS is 5 wt %, the mass fraction of MBA is 2.5 wt %, and the volume ratio of the solution, the APS aqueous solution and the MBA aqueous solution is 12:1:1, and the mixture is slowly stirred in a 45° C. water bath for about 30 min to obtain a PAA gel.

[0070] Comparative Example 2:

[0071] A method for preparing a fire-proof adhesive gel comprises the following steps:

[0072] (1) The nanoclay suspension is dissolved and mixed with dopamine to achieve dopamine intercalation, and a methylaminomethane-Tris buffer solution is added. Under alkaline conditions (usually pH value of about 8.5), dopamine undergoes in situ polymerization between nanoclay layers to form polydopamine (PDA);

[0073] (2) Weighing acrylic acid powder (2 wt%) and dissolving it in 10 mL of distilled water, heating it in a 45° C. water bath with stirring for 20 min to form a uniform solution;

[0074] (3) adding an aqueous sodium hydroxide solution to acrylic acid, and when the degree of neutralization of the acrylic acid reaches 70%, adding the sodium hydroxide solution to the solution formed in step (1) to obtain solution A, and adding an initiator potassium persulfate (APS) aqueous solution and a cross-linking agent N,N-methylenebisacrylamide (MBA) aqueous solution to solution A in sequence under stirring, stirring evenly, to obtain solution B;

[0075] (5) Solution B was slowly stirred in a 45°C water bath for 30 min to obtain PAA-DA gel.

[0076] Comparative Example 3:

[0077] A method for preparing a fire-proof adhesive gel comprises the following steps:

[0078] (1) Weigh sodium alginate powder and dissolve it in distilled water. Stir and heat in a 45°C water bath to form a uniform solution.

[0079] (2) dissolving dopamine in a sodium hydroxide aqueous solution, stirring at room temperature to fully dissolve it, and polymerizing to form a polydopamine (PDA) solution;

[0080] (3) mixing the polydopamine (PDA) solution obtained in step (2) with the sodium alginate (SA) solution obtained in step (1) and stirring to form a uniform SA / PDA solution;

[0081] (4) adding an aqueous sodium hydroxide solution to acrylic acid, and when the degree of neutralization of acrylic acid reaches 70%, adding the sodium hydroxide solution to the SA / PDA solution to obtain solution A, and sequentially adding an initiator potassium persulfate (APS) aqueous solution and a cross-linking agent N,N-methylenebisacrylamide (MBA) aqueous solution to solution A under stirring, and stirring evenly to obtain solution B;

[0082] (5) Solution B was slowly stirred in a 45° C. water bath to obtain a fire extinguishing adhesive gel (PAA-SA-DA gel) for use in mines after 20-30 min.

[0083] The properties of the adhesive gels obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were tested, and the specific method is as follows:

[0084] (1) Testing the adhesion strength of adhesive gel

[0085] The tensile adhesion test was conducted, and a variety of substrate surfaces were selected for adhesion test, including glass, coal, plastic and marble. The tensile sample size was set to 25.0mm×25.0mm×1.0mm, the stretching rate was set to 5mm / min, and the repeatability of the gel adhesion was evaluated by the tensile adhesion cycle test. The ratio of the maximum load to the adhesion area was defined as the adhesion strength.

[0086] (2) Testing the water retention properties of adhesive gel

[0087] Take a certain mass of adhesive gel and put it into a crucible, then put the crucible into a vacuum drying oven. The temperature of the vacuum drying oven is set to 100℃. Take out the crucible and weigh the mass every ten minutes, and record the data until the mass of the experimental sample does not change. Each group of samples is tested 3 times, and the average value is taken as the test result.

[0088] (3) Testing the plugging performance of adhesive gel

[0089] Use a small hammer to knock the fresh coal into coal blocks of different sizes, and then put the coal blocks of different sizes into the test tube so that the porosity in the test tube is 0.3. Secondly, the gel prepared in the embodiment and the comparative example is placed in a vacuum drying oven at 100°C for drying. When the gel quality remains unchanged, the gel is crushed and sieved to 40-60 mesh with a crusher. Then a visual self-adhesive gel diffusion experimental device is built, which is mainly composed of an acrylic container, a mine fire-proof adhesive gel material injection system, an air circuit system, and a monitoring system. Among them, the acrylic container is used to hold different fillers to simulate the coal rock state, size and other parameters in the goaf. The test tube is 25cm long and 12cm in diameter. The range of the pressure gauge is 0.4Mpa, and the flow meter is 10L / min. The system of adhesive gel material for fire prevention and extinguishing in mines mainly injects the material into loose coal; the gas path system is mainly composed of negative pressure vacuum pumps and related valves, simulating different air leakage volumes and air leakage speeds, and is used to determine the plugging effect of adhesive gel material for fire prevention and extinguishing in mines after injection. The monitoring system is mainly composed of pressure sensors and flow sensors, which are mainly used to monitor the changes of various parameters during the injection process and examine the plugging effect of gel through the changes in parameters. Finally, the plugging performance test is carried out. The specific process is as follows: first, the coal sample is placed in the test tube, and different types and concentrations of gel materials are injected respectively. The device is connected, the air tightness is checked, and the experiment is started. The plugging efficiency of the gel is calculated by changing the pressure and flow entering the device and recording the flow difference in the pipeline. First, we determine the pressure, adjust the flow, record the relevant data, and then adjust the pressure for a new round of testing. Each group is tested three times and the average value is taken.

[0090] (4) Testing the barrier properties of adhesive gel

[0091] Use a small hammer to knock the fresh coal into coal blocks of different sizes, grind them into coal powder, and use a 40-mesh sieve to filter out the 40-mesh coal powder. Then use a coal spontaneous combustion tendency tester and a gas chromatograph to conduct a resistance performance test. The test steps are as follows: First, fully mix the gel prepared in the embodiment and the comparative example with coal powder (40 mesh) at a mass ratio of 2:5. Under the same temperature and time conditions, the resistance rate is calculated by the difference between the indicator gas (CO) content generated by the coal sample pretreated with the gel during the coal spontaneous combustion process and the CO content released by the raw coal.

[0092] (5) Testing the fire extinguishing performance of adhesive gel

[0093] The fire extinguishing performance of the gel prepared in the embodiment and comparative example was tested by a small fire extinguishing device. Under the same conditions, the coal balls were placed on an electric furnace and heated for 25 minutes until they burned, and then the coal balls were placed in the combustion furnace, and the experimental device was turned on to collect data. After heating for 10 minutes, the three gels were evenly poured on the burning coal balls, and the temperatures of the two thermocouples were observed and recorded. One of the thermocouples measured the temperature in the middle of the two coal balls, and the other thermocouple measured the temperature on the top of the coal balls. To ensure the accuracy of the experiment, when the temperature in the middle of the two coal balls was 600°C, an equal amount (500mL) of gel was poured from above the coal balls, repeated 3 times, and the average value was taken as the experimental result.

[0094] The performance test results of the adhesive gels prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1.

[0095] Table 1 Performance test results of adhesive gel

[0096]

[0097] As can be seen from Table 1 above, in the air, the fire-proof adhesive gel for mines shows excellent adhesion strength to glass, coal, plastic and marble. Among them, the maximum adhesion strength of the fire-proof adhesive gel for mines to glass is 42Kpa, and the adhesion strength to coal is second to 36Kpa, while the gel prepared by Comparative Examples 1 and 2 shows poor adhesion performance, which shows that the nanoclay-polydopamine composite material has a decisive role in the adhesion performance of the gel. We tested the water retention performance of the gel after 24h and found that the water retention performance of the fire-proof adhesive gel for mines is 35% at best. The plugging efficiency of the gel under atmospheric pressure is tested. It can be seen that the plugging efficiency of the fire-proof adhesive gel for mines prepared in Example 1 is the highest, and its plugging efficiency can reach more than 95%, which also shows that it has a strong adhesion performance, so that the gaps between coal and gel, and between gel and gel are more compact, which is not conducive to the entry of airflow, thereby more effectively isolating coal from oxygen, preventing the oxidation of coal, and achieving the effect of preventing and controlling coal spontaneous combustion. It can be seen from the table that the fire-proof adhesive gel for mines in Example 1 shows excellent retardant performance compared with other gels, which can reach 52%. When the fire-proof adhesive gel for mines prepared in Example 1 is used for fire extinguishing, the temperature of the coal balls can be reduced by 84% and tends to be stable, and there is no re-ignition phenomenon. The gel prepared in Comparative Example 1 only reduces the temperature of the coal balls by 67%, while the gel prepared in Comparative Example 2 reduces the temperature of the coal balls by 83%. This shows that the fire-proof adhesive gel for mines has excellent fire extinguishing performance, because the fire-proof adhesive gel for mines can quickly gel after absorbing water, tightly wrap the coal balls, adhere to the surface of the coal gas, and can quickly reduce the temperature of the coal body and improve the fire extinguishing efficiency.

[0098] Parts not described in the present invention can be implemented by those skilled in the art by referring to the existing technology.

[0099] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present application and are not intended to be limiting of the present application. As long as they are within the spirit of the present application, appropriate changes and modifications to the above embodiments should fall within the scope of protection of the claims of the present application.

Claims

1. A method for preparing a fire-proof adhesive gel for use on the top of a coal mine goaf, characterized in that: The following steps are involved: (1) Preparing a sodium alginate solution: dissolving a certain amount of sodium alginate powder in distilled water, stirring and heating at a certain temperature to form a uniform solution; (2) preparing a nanoclay-polydopamine composite material: mixing a nanoclay suspension with dopamine, and then adding a buffer solution, so that under alkaline conditions, dopamine enters the interlayers of the nanoclay with a layered structure and polymerizes in situ to form a nanoclay-polydopamine composite material; (3) mixing the nanoclay-polydopamine composite material with the sodium alginate solution and stirring to obtain a mixed solution 1; (4) adding sodium hydroxide aqueous solution to acrylic acid for partial neutralization, and adding the mixed solution 1 to the neutralized solution to obtain a mixed solution 2; adding an initiator and a cross-linking agent to the mixed solution 2, and stirring to obtain a mixed solution 3; (5) The mixed solution is stirred at a certain temperature to form a gel. During the gelation process, acrylic acid is free radical polymerized under the action of an initiator and a cross-linking agent to form polyacrylic acid. The molecular chains of polyacrylic acid and sodium alginate form an interpenetrating grid structure through hydrogen bond interaction. The catechol groups contained in the nanoclay-polydopamine composite material form hydrogen bond interactions with the hydroxyl groups of polyacrylic acid and sodium alginate to obtain a fire-proof adhesive gel.

2. The method for preparing a fire-proof adhesive gel for use at the top of a coal mine goaf according to claim 1, characterized in that: In step (1), the mass fraction of sodium alginate in the sodium alginate solution is 1-3%, and the temperature is 40-50°C.

3. The method for preparing a fire-proof adhesive gel for use at the top of a coal mine goaf according to claim 1, characterized in that: In step (2), the preparation steps of the nanoclay suspension are: mechanically crushing bentonite and removing impurities; then wet grinding to peel off the layered structure of the bentonite into a nano-scale multi-layer structure; dispersing the bentonite obtained by mechanical crushing in water to form a uniform suspension.

4. The method for preparing a fire-proof adhesive gel for use at the top of a coal mine goaf according to claim 1, characterized in that: In step (2), the buffer solution is a methylaminomethane-Tris buffer solution, the pH value is 8-9 under alkaline conditions, and the mass ratio of the nanosuspension to dopamine is 1:

2.

5. The method for preparing the fire-proof adhesive gel for the top of the coal mine goaf according to claim 1, characterized in that: In step (3), the volume ratio of the nanoclay-polydopamine composite material to the sodium alginate solution is 1:

1.

6. The method for preparing the fire-proof adhesive gel for the top of the coal mine goaf according to claim 1, characterized in that: In step (4), sodium hydroxide aqueous solution is added to acrylic acid for neutralization, and after 70% neutralization, it is mixed with the mixed solution.

7. The method for preparing the fire-proof adhesive gel for the top of the coal mine goaf according to claim 1, characterized in that: In step (4), the initiator is a potassium persulfate solution, and the cross-linking agent is an aqueous solution of N,N-methylenebisacrylamide; the mass fraction of potassium sulfate in the potassium sulfate solution is 3-6%, and the mass fraction of N,N-methylenebisacrylamide is 2-3%; the volume ratio of the mixed solution II, the initiator, and the cross-linking agent is 12:1:

1.

8. The fire-proof and extinguishing adhesive gel prepared by the preparation method according to any one of claims 1 to 7.

9. The use of the fire-proof adhesive gel according to claim 8, characterized in that: The application is to spray the adhesive gel on the surface of coal to prevent spontaneous combustion of coal by reducing oxygen-containing functional groups of coal and isolating coal from oxygen.

Citation Information

Patent Citations

  • Fire prevention and extinguishing gel material for mine and preparation method thereof

    CN112354108A

  • Mine hydrogel fire preventing and extinguishing material and preparation method thereof

    CN117732003A

  • Steel slag-based mining fire preventing and extinguishing gel material and preparation method thereof

    CN118405864A

Cited By

  • Wide-temperature-range high-water-retention CO-inhibiting type fire preventing and extinguishing gel as well as preparation and application thereof

    CN122643642A